Aging : stability and change in the family - Fogel, Robert William; March, James G. (New York : Academic Press, 1981)
1. Aged--United States--Family relationship--Congresses 2. Aged--Government policy--United States--Congresses 3. Aged--Unites States--Sexual behavior--Congresses
Includes bibliographies and index
Faculty
Keywords: Older people -- Family relationships -- United States -- Congresses; Older people -- Government policy -- United States -- Congresses; Older people -- Sexual behavior -- United States -- Congresses